How to Plan and Schedule Conferences with the help of Artificial Intelligence. Issue 3 (9th June 2017) - Pan, Jason; Zou, Kelly H.; Yu, Ching-Ray; Sun, Franklin W.; Carlsson, Martin O.
Abstract: Months of conference planning can take mere minutes with a dash of optimisation. By Jason Pan, Kelly H. Zou, Ching-Ray Yu, Franklin W. Sun, and Martin O. Carlsson